Oral tradition and the discourse of poverty in pre-colonial South Nias: An interpretative study with a Foucaultian approach - Laiya, Juang Solala; Badaruddin, Badaruddin; Fikarwin, Fikarwin; Lubis, Zulkifli (Research Journal in Advanced Humanities, 2024)
This research examines the meaning of poverty in pre-colonial South Nias and its contrast with modern understandings of poverty. Adopting a qualitative-interpretative approach based on the paradigms of social constructivism and post-structural theories, it was applied to deconstruct two pre-colonial oral literature texts through the lens of Foucault's discourse analysis. Enriched by key informant interviews and related literature, the research uncovers two traditional Nias poverty terminologies that emphasize psychological well-being, attributing poverty more to a lack of happiness than material deprivation. The research also identifies three features of pre-colonial Nias poverty and the implicit cultural rules or epistemes that influence its construction. These results open up new perspectives on understanding the phenomenon of poverty in South Nias and emphasize the importance of policies that consider local wisdom such as collectivity, reciprocity, social exchange, and happiness in poverty reduction strategies. This research also highlights the importance of research into the social construction of local meanings of poverty as a foundation for the design of inclusive and culturally sensitive poverty reduction policies.